Arch Height Mediation of Obesity-Related Walking in Adults: Contributors to Physical Activity Limitations. (16th December 2014) - Gill, Simone V.; Lewis, Cara L.; DeSilva, Jeremy M.
Abstract : Walking and foot arch structure have risk-increasing effects that contribute to decreased physical activity in adults with overweight and obese body mass index (BMI) scores. However, it is unknown whether both excessive weight and arch height influence walking compared to the effects of excessive weight or arch height alone. The purpose of this study was to investigate if arch height mediates obesity-related walking characteristics among adults with different BMI classifications. Spatiotemporal walking kinematics and dynamic plantar pressure were collected as adults with normal( n = 30 ), overweight( n = 34 ), and obese( n = 25 ) BMI scores walked at their preferred speed. Digital footprints created with plantar pressure data were used to calculate a measure of arch height, the Chippaux-Smirak Index (CSI). The results showed that obese adults had lower arches than normal weight adults( P < 0.05 ) . Arch height was related to velocity, double limb support time, stance time, step length, and foot rotation (all P s < 0.05). Overweight participants with lower arches had lower velocities and higher double limb support times (all P s < 0.05). The results have implications for aiding an increase in physical activity for overweight adults via intervening in adults' arch height.